Explicit reading strategy instruction in an online reading classroom - Anit Pranita Devi; Suroto Suroto (ELT Forum: Journal of English Language Teaching, 2024)
Difficulties in comprehending English academic texts encountered by many students lead to the need for improvement in teaching reading. Moreover, in online reading instructions, explicit reading strategies are required so that students can develop their comprehension more independently and become strategic readers. This study aims to find out how explicit reading strategy instructions in online reading classes are implemented and what advantages and challenges are faced during its implementation. This is a case study program evaluation that uses observation, field notes, and interviews. It involves second-year students in an English literature study program taking a reading comprehension course. Despite several limitations, the results reveal that employing explicit reading strategy instructions in the online context can help students enhance their reading skills through structured and systematic phases. This is very much related to the advantage which shows an increase in student motivation in reading that further can improve students' reading ability in general and in comprehending English academic texts. However, these advantages are restricted by technological limits in the online learning process and student motivation variables. To maximize the effectiveness of explicit instruction in the online reading classroom, it is critical to invest in improved technological resources, integrate engaging and interactive content to increase student motivation and provide ongoing professional development for educators. These steps will help to ensure that explicit reading strategy instruction results in the best results possible.